Search for time lag in intra-day variability of Sgr A*. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Miyazaki, A.; Lee, S. S.; Sohn, B. W.; Jung, T.; Tsuboi, M.; Tsutsumi, T.
Abstract: We searched the time lag between the intra-day variables (IDVs) of Sagittarius A* at 22, 43, and 86 GHz bands using the Korean VLBI Network (KVN). The time lags between the IDV flare peaks at 22 and 43 GHz are reported, and they suggest that the flare emissions come from adiabatically expanding plasma blobs, ejected close to the Galactic center black hole. We searched the time lags between light curves at 90 and 102 GHz using the Nobeyama Millimeter Array, but could not find significant time lags. In order to detect the diversity of the time lags of Sgr A* flares, we performed observations of Sgr A* in the 22, 43, and 86 GHz bands using the KVN in the winter of 2013. Because the receiver system of KVN can observe Sgr A* in these three bands simultaneously, the KVN is very useful to detect the time lags of Sgr A* flares.